Dinamika Kualitas Hubungan para Pegawai DPRD Kota Palembang - Sabilla, Habiba Early; Itryah, Itryah (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
Employee interactions serve as a fundamental factor in creating conducive and productive work environments. Within legislative institutions like the Regional People's Representative Council (DPRD), interpersonal relationship quality influences the effectiveness of legislative, supervisory, and budgeting functions. The methodology employed observation and interviews to gather information from DPRD Kota Palembang employees. Community service results at the DPRD Kota Palembang office reveal that employee relationship quality plays a significant role in determining institutional performance effectiveness. However, ideal working relationships remain unrealized due to persistent communication barriers, minimal cross-departmental interactions, and rigid organizational culture. Addressing these challenges requires strategic efforts including strengthened internal communication, participative leadership, and work environment development that supports positive interactions and mutual trust. Such initiatives are expected to enhance individual and team performance while reinforcing DPRD's public service role.